EXPERIMENTAL STUDY OF SHEAR STRENGTH ANISOTROPY OF GRANULA MEDIUM CONSIDERING TECHNOLOGY FACTORS - Aniskin, A.; Shkola, A.; Premur, V. (Academic journal Industrial Machine Building Civil Engineering, 2017)
This article presents the results of experimental studies of the shear strength anisotropy of dry bulk material considering its preferred orientation of its flat particles to the shear plane as the effect of technological factors. The samples of a composite medium that was investigated, was mixture of silica sand with broken shells of mussels in a volume proportion 70% of sand and 30% of shells. Filling of the shear cell was conducted at different angles to the shear plane 0°, 30°, 60 ° and 90 °. For each angle of filling three series of experiments was conducted. Determined degree of anisotropy, as expected, was substantial, the largest difference in the angle of internal friction was 8% at an angles of filling 0° and 30°, and difference in the cohesion was 89,5% at an angles of filling 0° and 90° respectively. Keywords: anisotropy of shear strength parameters, fill technology, composite granular medium, direct shear test.